جهود علماء العربية في تيسير تعليم النّحو العربيّ للنّاطقين بغير العربيّة / The Contribution of Arab Linguists in facilitating learning Arabic grammar for non-Arabic speakers. - Dojan, Ahmed abdul Karim; Al Omari, Fatimah Mohamed Amin (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2017)
ملخّص البحث: يهدف هذا البحث إلى تأصيل البحث في مجال تعليم قواعد النّحو العربي للناطقين بغير العربية، من خلال البحث في تاريخ النّحو العربي عن أصول هذا المضمار، ويسعى البحث إلى تتبع أبرز محاولات النّحاة الأوائل -الذين وصلت إلينا آثارهم-في تيسير النّحو العربيّ للناطقين بالعربيّة وبغيرها من اللغات، وهم: خلف الأحمر، والجاحظ، وثعلب، وأبو علي الفارسي، وعبد القاهر الجرجاني، والزمخشري. وقد خلص البحث من خلال تتبّع آراء النّحاة السّالف ذكرهم والنّظر في مؤلّفاتهم إلى أنّهم التزموا في مؤلفاتهم منهجيّات واضحة، تميّزت بالتّنظيم والإيجاز، وابتعدوا عن المغالاة في الاستعانة بالمنطق والفلسفة والاعتماد على العلل، وأدركوا أهميّة التّطبيق، فعمدوا إلى الشّرح من خلال المثال والشّاهد. وقد كانت لهم آراء حاسمة في توضيح ما ينبغي تدريسه وما لا ينبغي، وانتبهوا إلى تصنيف الطلبة بالنّظر إلى مستوياتهم اللغويّة؛ المبتدئ والمتوسّط والمتقدّم، وخاطبوهم من خلال مؤلّفاتهم بما يتناسب مع أقدارهم واحتياجاتهم. الكلمات المفتاحيّة: النّحو العربي- العلماء، التيسير- النّاطقين بغير العربيّة. Abstract: This research aims to look into the field of teaching Arabic grammar for non- Arabic speakers, through studying the history and origin of Arabic grammar. The research seeks to track the most prominent attempts by grammarians in facilitating the learning of Arabic grammar for non-Arabic speakers namely: Khalaf al-Ahmar , al-Jāhez, Tha‘lab, Abu ‘Ali al-Fārisi, ‘Abd al-Qāher al-Jurjāni, and al-Zamakhsharī. Among the most important findings are: they committed in their compositions and writings to clear methodologies; they stayed away from excessive use of logic, systematic and brief. They avoided over reliance on philosophy and the logical grammatical causes while realizing the importance of the practical application, by giving examples and proofs. They were critical in clarifying the views of what should be taught and what should not, and paid attention to the classification of students given the different linguistic levels, beginners, intermediate and advanced; suggesting through their works the appropriate ways to address them according to their needs and capacity. Keywords: Arabic grammar- Scholars- facilitation- non-Arabic speakers. Abstrak: Kajian ini dijalankan untuk melihat secara mendalam bidang pengajaran tatabahasa Arab dengan menulusuri sejarah dan asal usul tatabahasa Arab itu sendiri. Ia akan mengesan usaha-usaha penting yang dilaksanakan oleh para ahli tatabahasa Arab dalam memudahkan pembelajaran tatabahasa Arab untuk penutur bukan Arab seperti: Khalaf al-Aḥmar, al-Jāḥiz, Abu ‘Ali al-Fārisi, ‘Abd al-Qāher al-Jurjāni, and al-Zamakhsharī. Antara dapatan terpenting kajian ini ialah: penulisan dan karangan mereka bersandarkan kepada metod yang jelas; mereka tidak menggunakan logic secara berlebihan, amat sistematik dan ringkas. Mereka juga cuba untuk tidak besandarkan kepada falsafah dan sebab logik tatabahasa di samping akur kepada kepentingan aspek praktikal dengan memberikan contoh dan bukti. Mereka juga amat kritis dalam menjelaskan pendapat-pendapat yang apa yang patut dan tidak patut di ajar dengan memberikan tumpuan kepada perbezaan antara pelajar serta tahap-tahap mereka seperti: pemulaan, pertengahan dan lanjutan; justeru memberikan cadangan tentang cara untuk mengambil kira tahap kemampuan dan kebolehan mereka. Kata kunci: Tatabahasa Arab- Pengkaji Bahasa Arab- Menudah cara- penutur-penutur bukan bahasa Arab.